ASSESSMENT OF HEALTH LITERACY OF ADULTS RECEIVING THEIR HEALTH CARE AT THE PIROT HEALTH CENTER AND THE FACTORS THAT DETERMINE IT - Gotić, Jelena; Markovic, Marko; Radovanovic, Jovana (HEALTH CARE, 2025)
Introduction/Aim: Health literacy is a concept that has been gaining increasing importance in the field of public health and healthcare, even though it has been in use since the 1970s. The aim of this work is to assess the level of health literacy in the population of adult patients who receive their health care in the Pirot Health Center, as well as to identify factors that may be associated with the level of health literacy.Methods: The research was conducted in the form of a cross-sectional study in the Pirot Health Center in the period from 1.5.2024. until 1.6. 2024. 400 respondents participated in the research. The general questionnaire and the European Health Literacy Questionnaire (HLS-EU-Q-47) were used as research instruments. The chi-square test was used in the statistical analysis of the data.Results: Out of 400 adult health center respondents, 10.2% had inadequate, 15.8% problematic, 33.5% sufficient, and 40.5% excellent health literacy. Sufficient or excellent health literacy was statistically significantly associated with gender, age, place of residence, marital status and level of education. Persons with chronic diseases, as well as persons who personally assessed that they have poor and very poor health status, significantly more often had inadequate/problematic health literacy.Conclusion: A low level of health literacy is a key barrier to the use of appropriate health care, which is why it is necessary to continuously work on the identification of groups with inadequate health literacy and their education.
Keywords: Health literacy, chronic disease, risk factors, public health